Isostatic stability of the East Antarctic station Dumont d’Urville from long-term geodetic observations and geophysical models - Amalvict, Martine; Willis, Pascal; Wöppelmann, Guy; Ivins, Erik R.; Bouin, Marie-Noëlle; Testut, Laurent; Hinderer, Jacques (Polar Research, 2009)
Geodetic measurements of the vertical crustal displacement collocated with absolute gravity changes provide a discriminatory measurement of present-day glacial changes, versus more deeply seated rock motions caused by glacial isostatic adjustment (GIA). At the East Antarctic station of Dumont d’Urville, we compare the displacements derived from continuous DORIS (1993.0– 2006.0) and Global Positioning System (GPS) (1999.0–2005.7) data, and observed changes in absolute gravity (2000–2006), with the predicted vertical displacement and change in gravity from GIA modelling. The geodetic results have mutual self-consistency, suggest station stability and provide upper bounds on both GIA and secular ice mass changes. The GIA models tend to predict amplitudes of rock motion larger than those observed, and we conclude that this part of Antarctica is probably experiencing a slight gain in ice mass, in contrast to West Antarctica.
Keywords: Antarktis; breendringer; geodesi; geofysikk; innlandsis; tidevannsmålinger

Revisiting sites of the South Pole Queen Maud Land Traverses in East Antarctica: Accumulation data from shallow firn cores - Anschütz, Helgard; Müller, Karsten; Isaksson, Elisabeth; McConnell, Joseph R.; Fischer, Helmut; Miller, Heinz; Albert, Mary; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2009)
[1] Ground-based accumulation measurements are scarce on the high East Antarctic plateau, but highly necessary for model validation and the interpretation of satellite data for the determination of Antarctic mass balance. Here, we present accumulation results obtained from four shallow firn cores drilled in the Antarctic summer season 2007/2008. The cores were drilled along the first leg of the Norwegian-US IPY traverse through East Antarctica, visiting sites like Plateau Station and Pole of Relative Inaccessibility that have been covered by the South Pole Queen Maud Land Traverses (SPQMLT) in the 1960s. Accumulation has been determined from volcanic chronology established from the conductivity records measured by dielectric profiling (DEP). The Tambora 1815/unknown 1809 double peak is clearly visible in the conductivity data and serves as a reliable time marker. Accumulation rates averaged over the period 1815–2007 are in the range of 16 to 32 kg m−2 a−1, somewhat lower than expected from the SPQMLT data. The spatial pattern is mainly influenced by elevation and continentality. Three of the firn cores show a decrease of more than 20% in accumulation for the time period 1815–2007 in relation to accumulation rates during the period 1641–1815. The spatial representativity of the firn cores is assessed by ground-penetrating radar, showing a rather smoothly layered pattern around the drill sites. Validation of the DEP results is utilized by comparison with chemistry data, proving the validity of the DEP method for dating firn cores. The results help understanding the status of the East Antarctic ice sheet and will be important for e.g. future model-derived estimates of the mass balance of Antarctica.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbreer; vulkaner

Ice-ocean processes over the continental shelf of the southern Weddell Sea, Antarctica: A review - Nicholls, Keith W.; Østerhus, Svein; Makinson, Keith; Gammelsrød, Tor; Fahrbach, Eberhard (Reviews of Geophysics, 2009)
Interactions between the Southern Ocean and the Weddell Sea ice shelves are important both to the Antarctic Ice Sheet and to the production of globally significant water masses. Here we review the interaction between the Filchner-Ronne Ice Shelf and the shelf sea in which it floats. The continental shelf processes leading to the production of Weddell Sea deep and bottom waters from the original off-shelf source waters are discussed, and a new view is offered of the initial production of High-Salinity Shelf Water. Data from ship-based measurements at the ice front, from glaciological methods, and from measurements made within the sub–ice shelf cavity itself are used to describe the pattern of flows beneath the ice shelf. We also consider the variability observed within the cavity from tidal to interannual time scales and finish with a discussion of future research priorities in the region.
Keywords: AABW; Antarktis; Sørishavet; Weddellhavet; glasiologi; innlandsis; isfront; isshelf; oseanografi; vannmasser